FORMATION OF TOLERANCE IN ADOLESCENTS (13-14 YEARS OLD) IN THE CONDITIONS OF THE MODERN EDUCATIONAL PROCESS - Mirsidikova Aziza Mirvohidovna (Bright Mind Publishing, 2025)
Important for the development of communicative tolerance in adolescents, successful communication in the social environment, working in collaboration with others and building relationships based on mutual respect.
Keywords: Adolescent child, tolerance, psychologist, educator, trait, development, communicative, period, ability, empathy, social, communication.